Design of A Structural Beam for Future UTP Composite Canopy - Mohd Irsyaduddin bin Ab. Latif, Mohd Irsyaduddin (Universiti Teknologi Petronas, 2009)
The objectives of this project are to design and analyze the current structure of UTP canopy and compare with the design made from composite material. The material to be used in this project is Glass Fibre Reinforced Epoxy (GRE) which is combination of woven E- Glass Fibre and Epoxy matrix. In this project, the current structure of the beam has been designed in CATIA V5 to estimate the volume and the mass of the structure.